Leadership Behavior And Job Satisfaction Among Bank Officers: The Impact Of Task Characteristics - Mat Desa, Nasina (Universiti Sains Malaysia, 2002)
The purpose of this study was to examine the relationship between leadership behavior and job satisfaction of bank officers in Penang and Kedah as perceived by the subordinates. The study chose three leadership styles as proposed by Sinha (1980) namely autocratic, participative and nurturant. The task characteristics performed by subordinates namely task structure, task autonomy and task variety were included as moderators to see the impact on the relationship between leadership behavior and job satisfaction.